Evaluation of the Effectiveness of the Use of Guiding Sutures in the Surgical Treatment of Children with Internal Ciliary Body - Erkinovich, Kasimov Rayim (American Journal of Biomedicine and Pharmacy, 2025)
Ophthalmoplegia is a paralysis of individual groups or all eye muscles. When the internal groups are affected, the pupils dilate and accommodation is impaired. The external form is manifested by diplopia, ptosis, and the inability to perform coordinated movements of the eyelids. For diagnosis, they use computed tomography of the brain, ultrasound of the eye, proserin test, and angiography of the cerebral vessels. In addition, skull radiography, visometry, and perimetry are used. Treatment tactics are determined by the etiology of the disease and include drug therapy, surgical interventions, and physiotherapy.